Analisis Dampak Stock Out Pada Gudang Sparepart 2 PT. XYZ Menggunakan Metode Stock Out Cost (SOC) - Azzami Nadhif Aulia’ (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2025)
This internship was conducted at the Planning, Receiving & Warehousing Department of PT. XYZ from January to February 2026. The objective of this internship was to analyze the impact of stockouts occurring in sparepart warehouse 2 using the Stock Out Cost (SOC) method. Data collection was carried out through direct observation, interviews with the field supervisor and warehouse staff, as well as documentation of historical data from the company's SAP system, specifically focusing on electrode and welding rod materials classified as fast-moving. Data analysis began with the Pareto method to identify materials with the largest inventory value contribution, followed by Stock Out Cost calculations to estimate financial losses due to material arrival delays exceeding the optimal lead time. The analysis results show that out of nine materials that experienced stockouts, three materials fall into category A (vital view), contributing 71.37% of the total affected inventory value. The SOC calculation for material with stock number 6029921(Electrode:E308L-3.2MM;STD LG) shows that a lead time delay of up to 119 days resulted in a financial loss of IDR 879,301 per KG. In addition to financial losses, stockouts also caused non-financial losses such as project completion delays, increased workload, and time inefficiency. This internship provides insight that stockouts are not always caused by inaccuracies in inventory control methods, but are more often influenced by non-technical factors such as the lack of synchronization between physical inventory in the warehouse and data in the SAP system.